Manipulative and Possessive: Exposing Jacqueline de Bellefort's Character - Ananda Citrasari; Endang Yuliani Rahayu (JELITA, 2024)
This study analyzes the ego defense mechanisms as well as the possessiveness and manipulative behavior of the character Jacqueline de Bellefort in the novel Death on the Nile by Agatha Christie. Jacqueline is shown as a character who is obsessed with her former fiancé, Simon Doyle, and exhibits extremely possessive and manipulative behavior after she marries Linnet Ridgeway. This study uses data analysis of qualitative research with text-oriented approach. Using psychoanalytic theory by Sigmund Freud, this study explores how Jacqueline uses ego defense mechanisms such as rationalization, projection, denial, and regression to deal with jealousy and rejection. The research reveals that Jacqueline's manipulative and possessive actions are a result of her internal conflict and inability to deal with her emotional reality, which ultimately drives her to extreme measures. The analysis is designed to provide broad understanding of Jacqueline De Bellefort and how she lives in defense mechanism.